An unusual case of interstitial lung disease: Revisiting peribronchiolar metaplasia interstitial lung disease (PBM‐ILD). Issue 2 (4th January 2023) - Jung, Flora; Shapera, Shane; Cabanero, Michael; McInnis, Micheal; Fisher, Jolene
Abstract: Peribronchiolar metaplasia (PBM) is a histological finding of uncertain significance commonly seen in interstitial lung disease (ILD). PBM is thought to be secondary to small airway injury from insults such as tobacco smoke and other environmental exposures. The term PBM‐ILD has been proposed for patients with ILD where PBM is the major histologic finding, however a lack of radiographic changes supportive of ILD in previously reported cases has limited recognition of the diagnosis. We present a rare case of welding‐associated ILD with clinical, radiographic, and histologic evidence consistent with the proposed definition of PBM‐ILD. We outline an approach to its consideration as a diagnosis based on our experience through multidisciplinary discussion. Abstract : We present a rare case of welding‐associated PBM‐ILD with clinical, radiographic, and histologic evidence consistent with the disease. We outline an approach to the diagnosis of PBM‐ILD based on our experience through multidisciplinary discussion.